Asymmetrical zinc(II) phthalocyanines conjugated to metal tungstate nanoparticles for photoinactivation of Staphylococcus aureus. Issue 7 (18th April 2022) - Mgidlana, Sithi; Managa, Muthumuni; Nyokong, Tebello
Abstract: In this study, we report for the first time on the photodynamic antimicrobial chemotherapy (PACT) of asymmetrical zinc(II) phthalocyanines and their conjugates with nickel tungstate (NiWO4 ), cobalt tungstate (CoWO4 ) and bismuth tungstate (Bi2 WO6 ) nanoparticles. CoWO4, NiWO4 and Bi2 WO6 were capped with glutathione and covalently linked to three asymmetrical zinc(II) phthalocyanines for PACT. The plate count method was used to investigate the effect of covalently linking asymmetrical zinc(II) phthalocyanines to nanoparticles under light (for PACT against Staphylococcus aureus ) and in the dark. Both Pc complexes and the conjugates indicated minimum dark-toxicity. The conjugates showed greater antimicrobial activity against a gram-positive and drug resistant bacteria, Staphylococcus aureus, than Pc complexes alone. GRAPHICAL ABSTRACT: UF0001